Primary Antimicrobial Susceptibility Changes in Children with Helicobacter pylori Infection over 13 Years in Northern Italy. (6th May 2015) - Manfredi, Marco; Gismondi, Pierpacifico; Maffini, Valentina; Bizzarri, Barbara; Fornaroli, Fabiola; Madia, Carmen; Salerno, Antonino; Cangelosi, A. Marta; de'Angelis, Gian Luigi
Abstract : The eradication therapy of Helicobacter pylori ( H. pylori ) infection is still a challenge for gastroenterologists. One of the main causes of failure in H. pylori eradication is the antibiotic resistance mainly to clarithromycin. Culture from biopsies is maybe the most used method among the antimicrobial susceptibility techniques. In this study, we compared the antimicrobial susceptibility changes in children with H. pylori infection over 13 years and we confirmed that clarithromycin resistance has been increased (16% versus 26%) though with no statistically signficant value. Therefore, clarithromycin should not be used in empiric treatment of H. pylori eradication therapy in children, but its use should be limited only to children with known antimicrobial susceptibility. On the other hand, metronidazole resistance has decreased over this time period in statistically significant manner (56% versus 33%, p = 0.014 ). Furthermore, ampicillin resistance has been confirmed to be very rare (3% versus 0%) in children with H. pylori infection. In conclusion, in H. pylori infection, if we do not know the antibiotic susceptibility of patients, we should recommend an eradication therapy based on the local distribution of antibiotic resistance rates trying to limit the therapeutic failures.